Body height, body mass, body mass index of elite basketball players in relation to the playing position and their importance for success in the game - Andelic, M.; Joksimovic, M.; Kukric, A.; Nikšic, E.; D'Angelo, S.; Zlojutro, N.; Skrypchenko, I.; Ceremidžic, D. (Acta Kinesiologica, 2021)
The morphological characteristics of elite basketball players are of great interest to some authors in order to define the best morphological profile for a particular playing position and different levels of competition. The aim of the research was to determine the differences in morphological characteristics in professional basketball players in relation to the playing position in different league competitions and to determine the relevance of these characteristics for success in the game. The survey included a sample of 773 elite basketball players competing in five different leagues in Europe. In our study, we found that centers are significantly taller and heavier than guards and forwards are. In addition to other components of basketball (technique, tactics, coach strategy), body height, body mass and body mass index play a major role in overall performance in a basketball game in all positions. The obtained data can help coaches in the scouting process in which leagues in Europe are played by players with certain morphological characteristics in relation to the playing position.